New occurrence of Phycodes templus Han and Pickerill, 1994 with a taxonomic reassessment of Yangziichnus yichangensis Yang, 1984 - Pickerill, Ron; Norman, Yolande; Han, Yaojun (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1995)
The ichnospecies Phycodes templus Han and Pickerill, 1994, previously only reported from the Lower Devonian Wapske Formation (Tobique Group) of New Brunswick, is described from the Lower Devonian Chapman Sandstone (Dockcndorff Group) of northeastern Maine. This recording extends the environmental range of the ichnospecies from deep-water basinal turbiditic strata of the Wapske Formation to storm-dominated shelf deposits of the Chapman Sandstone. Morphologically, Phycodes templus closely resembles the ichnotaxon Yangziichnus yichangensis Yang, 1984. Herein we recommend abandonment of the ichnogenus Yangziichnus and suggest assignment to Phycodes, namely Phycodes yichangensis comb. nov.